SEISMIC PROPERTIES OF THE UPPER MANTLE BENEATH LANZAROTE (CANARY ISLANDS): MODEL PREDICTIONS BASED ON TEXTURE MEASUREMENTS BY EBSD - Vonlanthen P.; Grobety B.; Kunze K.; Burlini L. (My University, 2006)
We present a petrophysical analysis of upper mantle xenoliths, collected in the Quaternary alkali basalt fields (Series III and IV) from the island of Lanzarote. The samples consist of eight harzburgite and four dunite nodules, 5 to 15 cm in size, and exhibit a typical protogranular to porphyroclastic texture. An anomalous foliation resulting from strong recovery processes is observed in half of the specimens. The lattice preferred orientations (LPO) of olivine, orthopyroxene and clinopyroxene were measured using electron backscatter diffraction (EBSD). In most samples, olivine exhibits LPOs intermediate between the typical single crystal texture and the [100] fiber texture. Occasionally, the [010] fiber texture was also observed. Simultaneous occurrence of both types of fiber textures suggests the existence of more than one deformation regime, probably dominated by a simple shear component under low strain rate and moderate to high temperature. Orthopyroxene and clinopyroxene display a weaker but significant texture.